PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PEMBIAYAAN SEKTOR UMKM PADA BANK UMUM SYARIAH DI INDONESIA - Mir’atul Amalia; Imam Azizuddin (Universitas PGRI Semarang, 2022)
The purpose of this study to analyze effect of internal and external factors on MSME financing in Islamic banks of Indonesia. The research sample used purposive sampling metod and optained 10 samples of Islamic Commercial Banks in Indonesia. The research data was sourced secondary data from the quarterly financial statements of each Islamic bank for period March 2016-June 2020 and produced 180 researces data. The research analysis used panel data regression with independent variables internal and external bank includes bank size, TPF, KPMM, ROA, NPF, FDR, inflation, and 7-day BI. The results of this study show that partially bank size, TPF, and CAR has a significant effect on MSME financing. However ROA, NPF, FDR, inflation, and BI 7-day have no significant effect on MSME financing. Bank size, TPF, KPMM, ROA, NPF, FDR, inflation, and BI 7-day have a significant effect on the allocation of MSME financing in simultaneously.